A Multilevel Model Of Organizational Commitment - (:unkn) unknown (ELSEVIER SCIENCE BV, 2011)
The relationship between job satisfaction and organizational commitment has been the subjects of a large amount of empirical researches. These researches have focused on either organization or individual level analysis, none of them examine individual variables and organizational characteristics simultaneously. In an effort to fill this theoretical gap, we use a multilevel structural equation modeling which integrated factors at both individual and organizational level to examine the relationship between job satisfaction and organizational commitment. The results based on 644 full-time bank employees from 63 bank branches indicate that job satisfaction is causally antecedent to organizational commitment both employee and branch level. (C) 2011 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of the 2nd World Conference on Psychology, Counselling and Guidance.
Keywords: Job satisfaction; organizational commitment; multilevel structural equation modeling; JOB-SATISFACTION; TURNOVER; ANTECEDENTS